Effect of Growth Space on The Productivity of Maize Using Three Sisters Cultivation with Bee Pollination - Nadia Damika Putri; Acep Purqon; Ramadhani Eka Putra (UIN Sunan Gunung Djati Bandung, 2023)
he increasing number of food needs is one of the driving factors for increasing agricultural production, but there are constraints on the availability of land. A polyculture system with corn, beans, and pumpkins, commonly known as the three sisters, can create positive interactions that can enhance the growth and development of each plant. This system has a vast potency to be applied to urban farming inside a grow bag because it does not require ample space, the placement of plants is flexible, and it produces a variety of yields. However, it is necessary to assess the effect of growing space on the growth of maize (Zea mays) cultivated by the three-sister system. This study used a completely randomized design with three treatments and six replications. The treatment consists of three planting spaces with various growing bags (treatment A:75 L, B:100 L, and C:200 L). The results of this study showed that the highest corn productivity was in the largest growing space (treatment C), which weighed 318.40 g/cob, and without husks 246.42 g/cob, but not significantly different from treatment B (grow bag 100 L), which weights 316.20 g/cob and without pods of 240.63 g/cob. This study found that the 100 L grow bag was the optimal growing space for planting corn in containers using the three sisters technique.